2020
DOI: 10.1002/dvdy.186
|View full text |Cite
|
Sign up to set email alerts
|

Fascin regulates protrusions and delamination to mediate invasive, collective cell migration in vivo

Abstract: BackgroundThe actin bundling protein Fascin is essential for developmental cell migrations and promotes cancer metastasis. In addition to bundling actin, Fascin has several actin‐independent roles; how these other functions contribute to cell migration remains unclear. Border cell migration during Drosophila oogenesis provides an excellent model to study Fascin's various roles during invasive, collective cell migration.ResultsOn‐time border cell migration during Stage 9 requires Fascin (Drosophila Singed). Fas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(52 citation statements)
references
References 60 publications
3
42
0
Order By: Relevance
“…We hypothesized that PGs may regulate the actin bundling protein Fascin to control border cell migration. This hypothesis is based on our prior finding that PGs regulate Fascin during S10B to promote actin remodeling ( Groen et al , 2012 ), Fascin is highly expressed in the border cell cluster ( Cant et al , 1994 ), and Fascin is required in both the border cells and the nurse cells for on-time border cell migration ( Lamb et al , 2020 ). To test our hypothesis, we used dominant genetic interaction studies.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We hypothesized that PGs may regulate the actin bundling protein Fascin to control border cell migration. This hypothesis is based on our prior finding that PGs regulate Fascin during S10B to promote actin remodeling ( Groen et al , 2012 ), Fascin is highly expressed in the border cell cluster ( Cant et al , 1994 ), and Fascin is required in both the border cells and the nurse cells for on-time border cell migration ( Lamb et al , 2020 ). To test our hypothesis, we used dominant genetic interaction studies.…”
Section: Resultsmentioning
confidence: 99%
“…We find that E-cadherin localization and levels appear grossly normal in pxt mutants (Supplemental Figure S4), indicating altered E-cadherin adhesions are not causing the cluster morphology defects. Interestingly, we previously reported that fascin mutant follicles display increased E-cadherin at both the border cell and nurse cell membranes ( Lamb et al , 2020 ). Thus, we hypothesize that Fascin’s function in regulating E-cadherin localization or expression is independent of PG signaling.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations